A mutation in the ftsK gene of Escherichia coli affects cell-cell separation, stationary-phase survival, stress adaptation, and expression of the gene encoding the stress protein UspA. - Diez, A A (1997)
An insertional mutation in ftsK, encoding an Escherichia coli product similar to the sporulation protein SpoIIIE of Bacillus subtilis, results in uspA overexpression in stationary phase and impairs cell division. The ftsK1::cat insertion mutant forms chains which are the result of inhibited cell-cell separation, while chromosome synthesis and partitioning appear to be normal as judged by flow cytometry and electron and light microscopy in combination with DNA staining. The cells of the chains are attached to each other by a small envelope structure, and unlike in a spoIIIE mutant of B. subtilis, there is no DNA trapped in the division plane. In addition, plasmids harboring a truncated ftsK allele lacking the last 195 bp of the gene cause chain formation in wild-type cells. While the mutant cells grow at essentially the same rate as the parent in complex and defined minimal media, they are sensitive to stresses. Specifically, the mutant failed to grow at elevated salt concentrations and survived stationary phase poorly. The phenotypes of the ftsK1::cat mutant are complemented by the 3' end (spoIIIE-like half) of the ftsK locus. In contrast, the 5' end of the ftsK locus reported to complement ftsK44(Ts) phenotypes does not complement the phenotypes of the ftsK1::cat mutant.